Analysis of Located Problems in Isfahan City-Region by Using of Social Network Analysis - Daryoush Moradi Chadegani; Masoud Ghasemi; Niloofar Rastghalam (تحقیقات کاربردی علوم جغرافیایی)
Isfahan City-Region is a collection of cities and towns with shareable common ground (such as communications, infrastructure, population and climate) at the geographical level of the city of Isfahan and its surroundings, and their social, economic, functional and spatial dependencies are such that one The geographically differentiated metamorphic and sub-regional divisions form the surface of the land and the main focus of its residential concentration is the city of Isfahan. These common features make it possible for them to complete complementary fields with single target targeting. Meanwhile, municipalities, as the main actor of urban management, play a major role in communicating cities and managing these relationships, so that these issues can play a common language among the actors in the city-region. This research is descriptive-analytic in terms of its main purpose. The analysis of locational problems and identification of key actors in Isfahan-Isfahan (including Isfahan and ten neighboring cities: Abrisham, Baharestan, Khomeinishahr, Khorzuq, Dorcheh, Dolatabad, Shahinshahr, Ghahjavarestan, Gaz, and Najafabad) is an applied research. For this purpose, in the first step, identifying problems between Isfahan and ten neighboring cities has led to the formulation of a statement of problems by using the dual paths of reviewing the documents of documents and urban plans and conducting interviews with city managers and experts. In the second step, analyzing the problems and problems of the cities located in the city-region of Isfahan, based on the six-tagged codes defined for each problem, the amount of weight (severity of the problem) is determined and, through the method of analyzing social networks, the network of "actors-problems" is drawn. Based on the findings of the analysis from this network, the problems of "Air pollution caused by the exhausted bus", "the occurrence of environmental problems caused by the destruction of the ecological capacity of West of Isfahan" and "shortage of fire fighting equipment in neighboring cities of Isfahan" are the most important of the city-region. The department of "Urbanism & Architecture", "Transportation" and "Urban Services" as acters paly the most key role in solving the problems of the city-region of Isfahan.